GoSAMTs are required for pectin methyl-esterification and mucilage release in seed coat epidermal cells - Parra-Rojas, Juan Pablo; Sepúlveda-Orellana, Pablo; Sanhueza, Dayan; Salinas-Grenet, Hernán; Temple, Henry; Dupree, Paul; Saez-Aguayo, Susana; Orellana, Ariel (Frontiers in Plant Science, 2023)
Introduction GoSAMTs play a role in the methylation of polysaccharides synthesized by the Golgi. Pectin homogalacturonan (HG) methyl-esterification is essential for the proper function of this polysaccharide in cell walls. In order to better understand the role of GoSAMTs in HG biosynthesis, we analyzed mucilage methyl-esterification in gosamt mutants. Methods To determine the function of GoSAMT1 and GoSAMT2 in HG methyl-esterification we utilized epidermal cells of seed coats, as these structures produce mucilage, which is a pectic matrix. We evaluated differences in seed surface morphology and quantified mucilage release. We measured methanol release, and used antibodies and confocal microscopy to analyze HG methyl-esterification in mucilage. Results We observed morphological differences on the seed surface and delayed, uneven mucilage release in gosamt1-1gosamt2-1 double mutants. We also found changes in the distal wall length indicating abnormal cell wall breakage in this double mutant. Using methanol release and immunolabeling, we confirmed that GoSAMT1 and GoSAMT2 are involved in HG methyl-esterification in mucilage. However, we did not find evidence of decreasing HG in the gosamt mutants. Confocal microscopy analyses detected different patterns in the adherent mucilage and a greater number of low-methyl-esterified domains near the seed coat surface, which correlates with a greater number of “egg-box” structures in this region. We also detected a shift in the partitioning between the Rhamnogalacturonan-I soluble and adherent layers of the double mutant, which correlated with increased amounts of arabinose and arabinogalactan-protein in the adherent mucilage. Discussion The results show that the HG synthesized in gosamt mutant plants is less methyl esterified, resulting in more egg-box structures, which stiffen the cell walls in epidermal cells and change the rheological properties of the seed surface. The increased amounts of arabinose and arabinogalactan-protein in adherent mucilage, also suggests that compensation mechanisms were triggered in the gosamt mutants.